Tuning the nanostructure of DODAB/nickel tetrasulfonated phthalocyanine bilayers in LbL films - Furini, L. N. [UNESP]; Feitosa, E. [UNESP]; Alessio, P. [UNESP]; Shimabukuro, M. H. [UNESP]; Riul, A.; Constantino, C. J L [UNESP] (Elsevier, 2013)
Nanostructured films of dioctadecyldimethylammonium bromide (DODAB) and nickel tetrasulfonated phthalocyanine (NiTsPc) were layer-by-layer (LbL) assembled to achieve a synergistic effect considering the distinct properties of both materials. Prior to LbL growth, the effect of NiTsPc on the structure of DODAB vesicles in aqueous medium was investigated by differential scanning calorimetry (DSC). Therefore, DODAB/NiTsPc LbL films were prepared using NiTsPc at concentrations below and above the limit concentration of vesicle formation according to our DSC experiments. As a result, LbL films with distinct nanostructures were obtained, which were studied at micro and nanoscales by micro-Raman and atomic force microscopy, respectively. A linear growth of the LbL films was observed by ultraviolet-visible absorption spectroscopy. However, the bilayer thickness and the surface morphology of the LbL films were radically affected depending on NiTsPc concentration. The electrostatic interaction between DODAB and NiTsPc was identified via Fourier transform infrared (FTIR) absorption spectroscopy as the main driving force responsible for LbL growth. Because LbL films have been widely applied as transducers in sensing devices, DODAB/NiTsPc LbL films having distinct nanostructures were tested as proof-of-principle in preliminary sensing experiments toward dopamine detection using impedance spectroscopy (e-tongue system). The real capacitance vs. dopamine concentration curves were treated using Principal Component Analysis (PCA) and an equivalent electric circuit, revealing the role played by the LbL film nanostructure and the possibility of building calibration curves. © 2013 Elsevier B.V.
Keywords: DODAB; e-tongue; LbL film; Nanostructures; Phthalocyanine; Dioctadecyl dimethylammonium bromides; Equivalent electric circuits; Fourier transform infrared absorption spectroscopy; Lbl films; Ultraviolet-visible absorption spectroscopy; Amines; Atomic force microscopy; Differential scanning calorimetry; Electronic tongues; Experiments; Fourier transform infrared spectroscopy; Materials properties; Neurophysiology; Principal component analysis; Sensors